Upaya Pasangan Suami Istri yang tidak mempunyai Anak dalam mempertahankan Harmonisasi Keluarganya - Abdul Malik Iskandar; Hasanuddin Kasim; Harifuddin Halim (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2019)
This research is to reveal (1) the childless couple's efforts to harmonize their marital relationships, (2) the efforts against stigma related to childless couples. This research is a quantitative descriptive using a survey approach. This research was conducted in East Pantar District, Alor Regency, East Nusa Tenggara (NTT) Province, Indonesia. The respondents were determined by using total sampling. Data collection techniques were carried out through questionnaires, interviews, and literature studies. Data were analyzed quantitatively using frequency tabulation and Likert Scale. The results showed that (1) The efforts to harmonize the marital relationships of childless couples are (a) internal efforts by strengthening communication and cooperation with a partner; (b) couples receive external support. (2) Efforts against stigma are (a) having positive thinking, (b) avoiding conflict, (c) avoiding sensitive talk. Based on the indicators, there were ten respondents' efforts to harmonize their marital relationships. This condition makes married couples have power and deal with the social stigma about them. The conclusion is that married couples make various efforts to harmonize their marital relationships and still hope to have children in their marriage life.